Evaluation of Headspace Solid-Phase Microextraction Gas Chromatography–Mass Spectrometry for the Characterization of Volatile Organic Compounds from Melon (Cucumis melo L.) Flowers - Silva, Francisca Aliny Nunes (2018)
Abstract: The secondary metabolism of plants plays a key role in plant–insect interactions. Among the various classes of metabolites produced, volatile organic compounds (VOCs) play important echophysiological roles, including the attraction of pollinators. This work aimed to develop a method to extract VOCs using headspace (HS) and solid-phase microextraction (SPME), which can be applied in future studies to contribute to the understanding of the role of VOCs in the pollination process. Therefore, a HS–SPME method combined with gas chromatography–mass spectrometry (GC–MS) was developed for the extraction and characterization of VOCs of melon flowers (Cucumis melo L.). The extraction was carried out with the fibers PDMS, DVB/CAR/PDMS and CAR/PDMS for the times 15, 30, and 45 min. Fifty compounds belonging to the following chemical classes were identified: terpenes, hydrocarbons, esters, ethers, ketones, aldehydes, and alcohols. CAR/PDMS fiber extracted the largest amount of compounds, and was more efficient for the extraction of volatile compounds with lower molecular weight, low boiling point and ideal for analytes in low concentration. Therefore, the evaluated method proved to be a promising tool for the analysis of VOCs of melon flowers, to be applied in new studies of the relationships between chemical composition and the processes of attraction of pollinators. Graphical Abstract: [Figure not available: see fulltext.].